Phonological development the first two years - Vihman, Marilyn May (Hoboken Wiley-Blackwell, 2014)
"Surveys what has been learned about phonological development in early infancy and raises questions for further study"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Language acquisition; Grammar, Comparative and general -- Phonology